The Competition Between the CDW and the Superconducting State in Valence Skip Compounds (Communications in Computational Physics, 2018)
In some superconductors the charge density wave (CDW) state is adjacentto the superconducting state in the phase diagram. This CDW phase can be collapsedeither pressure or by chemical doping, depending on compound. Among them, inso-called valence skip compounds, a large charge fluctuation with the large electron-phononinteraction is expected. We performed a first-principle study and investigatedhow the CDW gap is collapsed for several valence-skip compounds, i.e. SnX3, RbTlX3(X=F,Cl,Br,I) and CsTlI3. For all these compounds we found that the CDW gap israther robust for the uniform volume change, and on the contrary, the magnitude ofthe CDW gap strongly depends on the position of the anion. We found that this CDWgap is already collapsed at ambient pressure in SnBr3, SnI3 and CsTlI3.
Keywords: Valence skip; CDW; superconductivity; electronic structure; RbTlX$_3$; SnX$_3$; BaBiO$_3$.